Strategi Pengembangan Unit Usaha BUMDes Dalam Usaha Memenuhi Kebutuhan Dasar Masyarakat Desa Sidodadi Kecamatan Maliku Kabupaten Pulang Pisau (Studi Kasus: Unit Pengelolaan Air Bersih) - Ikaliskanawaty, Maria; Dwi Arta Qairi, Rakhinda (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Village-Owned Enterprises (BUMDes) are a form of business entity that protects the ongoing activities of village-owned businesses, whether they are based on legal entities or not based on law. The early history of the pioneering of Village-Owned Enterprises (BUMDes) is a manifestation of the mandate of Village Law no. 6 of 2014 with the hope of developing and preserving assets so that economic independence in rural areas is achieved. The establishment of Village-Owned Enterprises (BUMDes) can be carried out by each Village Government. However, in its stance, BUMDes was founded on the initiative of village communities which is based on potentials that can be developed, improved or optimized by means of the use of original and local resources and the presence of market demand. BUMDes is a place to meet the needs of village communities by trying to accommodate all community economic activities based on the potential of a village.